Dynamic of migration and labor productivity in the rural area of PATANAS villages. Issue 1 (November 2021) - Irawan, A R; Ashari,; Sudaryanto, T; Irawan, B; Sunarsih,; Nida, F S
Abstract: The agricultural sector still becomes a source of household income in rural areas, although its role tends to decrease. In the period 2011‒2015, the number of agricultural workers decreased about 1% per year and is inversely proportional to the increasing Indonesian labor, which reached an average of 1.2% per year. Several leading causes of labor decreases are migration and productivity issues in the agricultural sector. This paper aims to determine migration and labor productivity dynamics in three-time points in villages on Panel Petani Nasional Program (PATANAS) located at three agroecosystems: plantation, secondary crop, and vegetable. Amount of respondents in each agroecosystem were 312, 232, and 121 farmers. Data analysis was presented descriptively. The results of the study indicated that labor productivity varies between agroecosystems. The highest increase in productivity occurred in vegetable, then secondary crop, and plantation. Labor productivity in the agricultural sector is inversely proportional to the migration on an agroecosystem. There is not excessive migration in the vegetable agroecosystems since labor productivity is highest than the others. There is a phenomenon of increasing working family members followed by an increase in the number of migrations. This phenomenon negatively impacts the agricultural sector because there is no increase in the number of workers in the agricultural sector. There is a trend for young people in PATANAS villages to undertake permanent migration. Increasing labor productivity in rural areas predicted could reduce labor migration. Efforts that can be created are gradually encouraging off-farm and non-farm activities, including small-scale agro-industries.